Strategy Implementation in Bank Performance Achievement Based on The Balanced Scorecard - Rieke Sri Rizki (TRIKONOMIKA, 2017)
The purpose of this research was to know the influence of strategy implementation to the performance achievement of bank based on the balanced scorecard. The research had been done on Branch Office (BO) of Bank Bjb in West Java. Explanatory case study type was used as the research design. The population included all the functional managers (heads of division) of all BO of Bank Bjb in West Java. There were 48 heads of division in 16 BO with purposive sampling method. Data type was cross-section and questionnaire that were given to three functional managers. Path analysis was used. The result showed that the strategy implementation which had been done in credit management, credit supervision and recovery management, also fund and service management, simultaneously and partially had positive influence in the performance achievement of bank based on the balanced scorecard.